Gait efficiency of walking robots - Silva, Manuel (2002)
This paper studies periodic gaits of multi-legged robot locomotion systems based on dynamic models. The purpose is to determine the system performance during walking and the best set of locomotion variables. For that objective the prescribed motion of the robot is completely characterized in terms of several locomotion variables such as gait, duty factor, body height, step length, stroke pitch, foot clearance, legs link lengths, foot-hip offset, body and legs mass and cycle time. In this perspective, we formulate three performance measures of the walking robot namely, the mean absolute power, the mean power lost in the joint actuators and the mean force of the interface body-legs per walking distance. A set of model-based experiments reveals the influence of the locomotion variables in the proposed indices.